ANALISIS KEBIJAKAN IMPOR BERAS 1 JUTA TON OLEH PEMERINTAH INDONESIA: DATA DAN ANALISIS MEDIA SOSIAL - Zahra Mahreva Basuki; Rizky Juda Putra Hidayat; Puji Susilo Asih; Iradhad Taqwa Sihidi (Universitas Jenderal Ahmad Yani, 2021)
The rice import plan to be carried out by the Indonesian government is a very interesting issue to discuss considering that Indonesia is known as an agricultural country. Based on data shown by BPS in 2017, around 29.76% of Indonesia's population works as farmers. This means that when rice import activities are carried out, the welfare of 31.68 million people (farmers) will experience a decline. This study aims to analyze the Indonesian government's plan to import 1 million tonnes of rice, from the perspective of the community that is broadcast on the data and analysis on social media. Meanwhile, data and social media analysis can be seen on (Twitter) obtained through Drone Emprit in the period 13-19 March 2021. The results found based on the data displayed by Drone Emprit show that the issue or plan to import 1 million tons of rice is an inviting policy. many pros and cons in society. The policy for rice imports is strongly rejected by the majority of Twitter people because farmers will enter the main harvest, which is when rice imports continue, what happens is a decrease in the selling price of rice from farmers. And as a result, the farmers will experience a lot of losses.